Competitive intelligence and strategy formulation: connecting the dots. Issue 2 (13th May 2020) - Cavallo, Angelo; Sanasi, Silvia; Ghezzi, Antonio; Rangone, Andrea
Abstract : Purpose: This paper aims to examine how competitive intelligence (CI) relates to the strategy formulation process of firms. Design/methodology/approach: Due to the novelty of the phenomenon and to the depth of the investigation required to grasp the mechanisms and logics of CI, a multiple case study has been performed related to four companies located in Brazil that adopted CI practices within dedicated business units to inform and support strategic decision-making. Findings: The authors provide detailed empirical evidence on the connection and use of CI practices throughout each stage of the strategy formulation process. Moreover, the study suggests that CI practices, despite their strategic relevance and diffusion, are still extensively adopted for tactical use. Originality/value: This study sheds light on how CI practices may inform, support, and be integrated in the strategy formulation process, as few studies have done before.